THE ROLE AND IMPORTANCE OF FOREIGN INVESTMENT IN ECONOMIC DEVELOPMENT - Xabibullayev Baxtiyor Abdulvoxid ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article talks about the fact that attracting and using foreign investments based on world experience convincingly proves how much they contribute to economic development and serve as a powerful incentive for socio-economic reforms.